2018
DOI: 10.1111/hsc.12595
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roles and factors influencing community health workers’ performance in managing and referring severe acute malnutrition cases in two subdistricts in South Africa

Abstract: As primary providers of preventive and curative community case management services in low- and middle-income countries (LMICs), community health workers (CHWs) have emerged as a formalised part of the health system (HS). However, discourses on their practices as formalised cadres of the HS are limited. Therefore, we examined their role in care, referral (to clinics) and rehabilitation of severe acute malnutrition (SAM) cases. Focusing on SAM was essential since it is a global public health problem associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Two studies examined alcohol-related policies [ 35 , 68 ] where one study scrutinised illegal drug policies [ 37 ]. Three studies explored nutrition: two focusing on malnutrition management and prevention in UMICs [ 56 , 62 ] and one reviewing school food policy development and implementation in the Philippines [ 74 ]. Interestingly, all three mental health policy analysis studies included in this review focused on the topic of child, and mostly, adolescent mental health policy [ 45 , 63 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies examined alcohol-related policies [ 35 , 68 ] where one study scrutinised illegal drug policies [ 37 ]. Three studies explored nutrition: two focusing on malnutrition management and prevention in UMICs [ 56 , 62 ] and one reviewing school food policy development and implementation in the Philippines [ 74 ]. Interestingly, all three mental health policy analysis studies included in this review focused on the topic of child, and mostly, adolescent mental health policy [ 45 , 63 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The full assessment should include mid‐upperarm circumference (MUAC) measurement, plotting and interpreting weight for height, an examination of oedema, a clinical examination for Integrated Management of Childhood Illnesses (IMCI) danger signs and an appetite test [ 6 ]. However, CHWs lack adequate training, require better supervision and essential resources, and are sometimes inhibited from performing stabilisation care before referral due to restrictive policies [ 7 ]. As a result, in most areas in South Africa, screening by CHWs only include measurement and interpretation of MUAC and to assess for the presence of oedema, followed by referral to the nearest primary health care centre.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve SDG 3.2, efforts to reduce preventable deaths of under-five children, SSA should strive to identify and address bottlenecks to the successful implementation of SAM management guidelines [5,26]. In previous studies, the limitations of managing SAM at the SA community level have been identified [27] and the comprehensiveness of SA's SAM guidelines has been appraised [28]. To enhance the narrative, this study explored the complexity of implementing SAM guidelines by focusing on the diagnosis, management, and referral of underfive children within the rural subdistrict's referral system and the factors influencing these practices.…”
Section: Introductionmentioning
confidence: 99%